1978
DOI: 10.1002/1097-4679(197804)34:2<484::aid-jclp2270340249>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating and debilitating test anxiety among college students and volunteers for desensitization workshops

Abstract: Administered the Alpert-Haber Achievement Anxiety Test (AAT) to 54 students who expressed interest in participating in a test anxiety desensitization workshop. In addition, 182 students from the general college population were tested. Results indicated that both the debilitating and facilitating (AAT) scales were higher for the self-referred volunteer group. These data indicate that these scales are useful in distinguishing self-referred volunteers for behavior modification workshops from a general college pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…the Achievement Anxiety Test, AAT) provided a significantly stronger predictor of academic performance than a conventional debilitating anxiety scale. Subsequent investigations employing the AAT reported by, among others, Munz, Costello & Korabek (1975), Hudesman & Wiesner (1978, Gaeddert & Dolphin (1981), Couch, Garber & Turner (1983, and Carrier, Higson, Klimoski & Peterson (1984) are all examples of studies which demonstrate the value of distinguishing between debilitating and facilitating anxiety. Wine's (1980) bidirectional model of test anxiety further supports the notion of positive and negative dimensions in arguing for this greater specificity of the state anxiety response.…”
Section: Muftidimensionaf Competitive Anxieg and Performancementioning
confidence: 98%
“…the Achievement Anxiety Test, AAT) provided a significantly stronger predictor of academic performance than a conventional debilitating anxiety scale. Subsequent investigations employing the AAT reported by, among others, Munz, Costello & Korabek (1975), Hudesman & Wiesner (1978, Gaeddert & Dolphin (1981), Couch, Garber & Turner (1983, and Carrier, Higson, Klimoski & Peterson (1984) are all examples of studies which demonstrate the value of distinguishing between debilitating and facilitating anxiety. Wine's (1980) bidirectional model of test anxiety further supports the notion of positive and negative dimensions in arguing for this greater specificity of the state anxiety response.…”
Section: Muftidimensionaf Competitive Anxieg and Performancementioning
confidence: 98%
“…For example, Carrier, Higson, Klimoski, and Peterson (1 984), Couch, Garber, and Turner (1 983), and Hudesman and Wiesner (1978), all provided evidence which supports the merits of distinguishing between debilitating and facilitating anxiety in this context. Wine (1 980) also offered support for the notion of even greater specificity of state anxiety in proposing the bidirectional model of test anxiety, which was based around these positive and negative conceptions of the response.…”
mentioning
confidence: 93%
“…Instruction and assessment must complement the complex nature of knowledge and take place in a form that makes the process of knowledge construction and transformation observable to some extent. Hudesman and Wiesner [16] found that attrition and debilitating anxiety are not in any logical relationship with each other. facilitating anxiety however functions in terms of a scale to the language learners' ego strength in forecasting workshop attendance.…”
Section: Srphmentioning
confidence: 99%